Reinforcing the Efficiency of Plastic Upgrading through Full‐Spectrum Photothermal Effect Integration of Heat Isolator - Xueqin Gong; Peng Wang; Shuo Yang; Wenbo Li; Min Lv; Bei Li; Xiangxiang Zhang; Zeyan Wang; Yuanyuan Liu; Peng Wang; Hefeng Cheng; Ying Dai; et al. (Advanced Science)
Abstract Photoreforming of polyethylene terephthalate (PET) to H2 is practically attractive strategy for upgrading waste plastics. The major challenge is to utilize the infrared energy in the solar spectrum to improve the efficiency for photoreforming of PET to H2. Herein, through the ingenious integration of tungsten phosphide nanoparticles and tungsten single atoms (WP/W SAs) with carbon nitride (g‐C3N4), the constructed hybrid inherits both the desirable properties and structural merits of the respective building blocks. Specifically, the photothermal effect of WP/W SAs couples with the “heat isolator” role of g‐C3N4 due to its low thermal conductivity, thereby forming localized high‐temperature regions, reducing the activation energy and improving the kinetics in the photoreforming of PET to H2. Additionally, the green pretreatment of PET using alkali‐free hydrothermal strategy is reported, achieving direct separation of the ethylene glycol and terephthalic acid. This work not only provides an alkali‐free hydrothermal pretreatment for PET, but also integrates the photothermal effect with the thermal insulation and opens a new avenue for harnessing solar energy into to convert plastics into H2.